Social Welfare, 1850–1950 - Platt, Desmond Christopher St.Martin. author. aut Link
XII, 208 p.
Keywords: This historical study of the development of social welfare systems in divergent countries draws on a variety of essays to examine the work of each country in turn, followed by a comparison of all three and an examination of social experiments in regions of recent settlement.